CARDIORESPIRATORY ARREST AND NURSING: THE KNOWLEDGE ON BASIC LIFE SUPPORT - Cristiele Aparecida Alves; Cinthia Natalia Silva Barbosa; Heloisa Turcatto Gimenes Faria (Universidade Federal do Paraná, 2013)
The objective of this descriptive and cross-sectional study was to assess the theoretical knowledge of the nurses in a hospital in the state of Minas Gerais regarding the basic life support used in attending cardiorespiratory arrest. The sample was constituted by 16 nurses, and an instrument constructed based on the recommendations of the American Heart Association for cardio-pulmonary resuscitation was used for data collection. The results showed gaps in the knowledge on the rhythms identified in cardio-respiratory arrest, the sequence of steps, number of cycles versus ventilation, opening of the airways, where to place the defibrillator electrode pads, the procedure to be undertaken immediately after the shock, and the loads, in joules, recommended for the defibrillation. The re-assessment and continuous training of the nurses is recommended, for their adequate performance in treating cardiorespiratory arrest, contributing to the population's survival.